2021
DOI: 10.1016/j.ijscr.2021.106076
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic pseudoaneurysm of the superficial temporal artery following craniectomy from a scalp hook retractor penetrating injury: Case report and literature review

Abstract: Background Iatrogenic pseudoaneurysms in scalp vessels are an uncommon complication after cranial surgery. This paper reports a case of scalp pseudoaneurysm in the superficial temporal artery (STA) after forceful hook retraction in craniectomy and reviews the relevant literature. Case description A 36-year-old man with history of hypertension and depression presented to the emergency department with head injury after using sedation medication. Brain computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several reports highlighted the occurrence of iatrogenic pseudoaneurysms in different scenarios. Zheng et al reported iatrogenic pseudoaneurysms of the STA resulting from vessel penetration with a needle or hook, or injury to the vessel wall during craniotomy [24]. Protecting vessels during harvesting and conducting thorough imaging evaluations postbypass surgery are emphasized, as illustrated by a past case where pseudoaneurysm rupture after STA-MCA anastomosis caused massive intracerebral hemorrhage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports highlighted the occurrence of iatrogenic pseudoaneurysms in different scenarios. Zheng et al reported iatrogenic pseudoaneurysms of the STA resulting from vessel penetration with a needle or hook, or injury to the vessel wall during craniotomy [24]. Protecting vessels during harvesting and conducting thorough imaging evaluations postbypass surgery are emphasized, as illustrated by a past case where pseudoaneurysm rupture after STA-MCA anastomosis caused massive intracerebral hemorrhage [25].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Reported causes of STA damage include subcutaneous suture needles, hook retractor, or three-point pin fixators. [6][7][8]13,16 Systemic diseases including hemophilia or vasculitis, and background such as triple H therapy after subarachnoid hemorrhage, are also risk factors for pseudoaneurysms. 6,9,11,12 Furthermore, even if there is only endothelial damage without bleeding, surgical manipulation or electrocoagulation may lead to formation of fusiform dilatation and subsequent minor bleeding, resulting in pseudoaneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of pseudoaneurysms after craniotomy are rare, with only 16 cases in the literature (►Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Reported causes of STA damage include subcutaneous suture needles, hook retractor, or three-point pin fixators. [6][7][8]13,16 Systemic diseases including hemophilia or vasculitis, and background such as triple H therapy after subarachnoid hemorrhage, are also risk factors for pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we present left anterolateral thigh (ALT) flap 2) harvesting using scalp hooks 3) as retractors. The usage of scalp hooks largely addressed the abovementioned concerns, demonstrating their excellent superiority over traditional retractors.…”
Section: Introductionmentioning
confidence: 99%